2022
DOI: 10.1002/tox.23480
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin inhibits cancer cell migration and matrix metalloproteinases‐2 expression in human nasopharyngeal carcinoma through extracellular signal‐regulated kinase signaling pathway

Abstract: Nasopharyngeal carcinoma (NPC) is endemic in Southeast Asia and the main cause of treatment failure is metastasis. A lot of biological and pharmacological actions of dihydromyricetin (DHM) have been reported such as regulating glucose and anticancer effects. The effects of DHM on the cancer invasion and migration of NPC, however, are still unclear. We therefore investigated the in vitro anti-metastatic properties of DHM on three human NPC cell lines (HONE-1, NPC-39, and NPC-BM), as well as the underlying signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Matrix metalloproteinases, a family of zinc-dependent proteinase, have long been associated with tumor cell invasion and metastasis for its ability in activating cancer cells, modulating immune function, degrading extracellular matrix and basement membrane. [25][26][27][28] In particular, matrix metalloproteinase-9 (MMP-9) has been widely investigated to relate to the pathology of cancer. [29][30][31] TPA (12-O-Tetradecanoylphorbol-13-acetate), a phorbol ester, has been well-documented on cancer metastasis in several cancer types.…”
mentioning
confidence: 99%
“…Matrix metalloproteinases, a family of zinc-dependent proteinase, have long been associated with tumor cell invasion and metastasis for its ability in activating cancer cells, modulating immune function, degrading extracellular matrix and basement membrane. [25][26][27][28] In particular, matrix metalloproteinase-9 (MMP-9) has been widely investigated to relate to the pathology of cancer. [29][30][31] TPA (12-O-Tetradecanoylphorbol-13-acetate), a phorbol ester, has been well-documented on cancer metastasis in several cancer types.…”
mentioning
confidence: 99%
“…In an in vivo experiment on mice transplanted with B16 melanoma cells, Zheng et al ( 68 ) reported that mice given DHM at doses of 150, 200 and 250 mg/kg exhibited a significant reduction in the number of metastatic tumours compared with those in the control group, demonstrating the anti-invasive and anti-metastatic effects of DHM on B16 melanoma. Moreover, DHM inhibits the migration and invasion of nasopharyngeal carcinoma cells by suppressing the ERK1/2 signalling pathway and suppressing MMP-2 expression ( 69 ); it also inhibits the proliferation, migration and invasion of CAA HCCC9810 and TFK-1 cells by regulating miR-21 and promoting apoptosis ( 70 ) ( Fig. 3 ).…”
Section: Multiple Molecular and Cellular Mechanisms Of The Antitumour...mentioning
confidence: 99%
“…DHM can silence the activation of p-IKKβ/α, block the nuclear translocation of NF-κB subunit p65, significantly suppress TNF-α-mediated NF-κB activation in CNE-2 cells, and reduce the expression levels of Bcl-2 and pro-caspase-3, resulting in CNE-2 cell apoptosis [ 105 ]. Moreover, DHM can inhibit the migration and invasion of NPC cells by suppressing the expression of MMP-2 by downregulating the ERK1/2 signaling pathway [ 106 ]. Figure 1 shows the anticancer mechanism of DHM.…”
Section: The Anticancer Potential and Underlying Mechanisms Of Dihydr...mentioning
confidence: 99%